2000
DOI: 10.1088/0031-9155/45/2/314
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between CT numbers and tissue parameters needed for Monte Carlo simulations of clinical dose distributions

Abstract: We describe a new method to convert CT numbers into mass density and elemental weights of tissues required as input for dose calculations with Monte Carlo codes such as EGS4. As a first step, we calculate the CT numbers for 71 human tissues. To reduce the effort for the necessary fits of the CT numbers to mass density and elemental weights, we establish four sections on the CT number scale, each confined by selected tissues. Within each section, the mass density and elemental weights of the selected tissues ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
724
0
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(737 citation statements)
references
References 19 publications
2
724
0
11
Order By: Relevance
“…For the present treatment of voxel computational phantoms referred to the adult reference male of ICRP 110 publication [19] we have compiled its CT values [20] formed by the DICOM format to the PHITS input data using the "dicom2phits" package program combined with the PHITS calculation code. This program has involved the data exchange functions based on the relationship between CT values [19,20] and material densities and compositions at each tissue or organ [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present treatment of voxel computational phantoms referred to the adult reference male of ICRP 110 publication [19] we have compiled its CT values [20] formed by the DICOM format to the PHITS input data using the "dicom2phits" package program combined with the PHITS calculation code. This program has involved the data exchange functions based on the relationship between CT values [19,20] and material densities and compositions at each tissue or organ [14].…”
Section: Methodsmentioning
confidence: 99%
“…This program has involved the data exchange functions based on the relationship between CT values [19,20] and material densities and compositions at each tissue or organ [14]. In the present PHITS input file, we have generated the voxel phantom data with the smallest unit size of 0.98 0.98 10 mm 3 for each compartment of the respiratory tract regions around a human lung.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue segmentation is performed by the formalism in Schneider et al, (10) as reported earlier (6) . Clinical target volume (CTV) and planning target volume (PTV) are delineated according to clinical routine at our hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The correspondence between each voxel CT number and its material is established by calibration functions, which are CT scanner dependent. For the used scanner, a Siemens Somatom Plus 4, CT number conversion to elemental weights of tissue and mass density were obtained following the work of Schneider et al [16]. These authors have divided the CT number range, comprehended between −1000 Hounsfield to 1500 Hounsfield, in different regions, each one having a distinct density and elemental weights of tissue parameterization.…”
Section: Geometry Implementationmentioning
confidence: 99%
“…A CT thorax image was acquired and two regions composed of different radiological substitute tissues were identified, Rando-lung and Randotissue [20], and the CT-number distributions obtained. Mean CT values were then used to calculate a mean density value for this tissue using parameterizations described in [16]. Results were compared with manufacturer data and are presented in Table 1.…”
Section: Ct Interface Validationmentioning
confidence: 99%